KONSTRUKSI IDENTITAS KE-PAPUA-AN DI KOTA MULTI KULTURAL (REFLEKSI KOTA YOGYAKARTA DALAM KAJIAN IDENTITAS - Abbas, Moh Rafli (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
The main aim of this writing is to analyze the formation of an identity conducted by students of Papua in expressing their ethnicity in Yogyakarta. The expression of their ethnic identity put forward in the public sphere is a strong indication that Papuan students in Yogyakarta reproduced their ethnic identity to represent their continuous struggle to be properly acknowledged and appreciated. Their expression of identity is a living proof of the existing political struggle as Papuan students in Yogyakarta to unhide their feeling of being neglected and discriminated among and by their fellow Indonesians.